PEMBINAAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) OLEH DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI RIAU - Leni Yumaida Putri; Mimin Sundari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The development of a successful Occupational Safety and Health Management System (SMK3) is one of the supporting factors for the success of the K3 coaching that has been implemented. Riau Province received an award as the best K3 coach nationally from the Ministry of Manpower for the last five years but in fact the guidance carried out is not directly proportional to this award. The purpose of this study shows how the guidance carried out by the Riau Province Manpower and Transmigration Office on the occupational safety and health management system in the company and to find out the inhibiting factors. This research uses Santoso coaching theory (in Harifal, 2014) which uses indicators, namely: Providing guidance, giving direction, providing education and training, and providing instructions. This study uses a qualitative method. The results of this study found that the development of an occupational safety and health management system by the Department of Manpower and Transmigration of Riau Province has not been implemented optimally, this is due to several inhibiting factors, namely human resources that are not proportional to the number of companies that must be fostered, the division of work locations. wide area so that it is difficult to reach them and an inadequate budget to carry out all activities so that coaching activities do not run optimally.